Climate Change And The Truth Behind Data - Mouzouropoulos, Theseas (My University, 2023)
The 5th Emirates International Poster Festival (EIPF) centered around the theme “Design for Climate Change,” where creativity and innovation converge to address the pressing global concern of climate change. This edition of EIPF coincides with the UAE’s hosting of the 28th Conference of the Parties to the UN Framework Convention on Climate Change (COP28) in November 2023 at Expo City Dubai. This edition of EIPF showcases the significant role of design in raising awareness about climate issues and providing innovative solutions to construct a sustainable and resilient world. The Emirates International Poster Festival (EIPF) stands as a distinctive and creative platform in the MENA region, dedicated to presenting and honoring contemporary poster design from across the globe. Initiated by the Cultural and Scientific Association (NADWA) in Dubai, this festival aims to foster and amplify creative expression while advancing graphic design practice and innovative thinking within the MENA region. Posters, in their invaluable capacity for visual communication, serve to convey information, human thoughts, responses to local and global matters, and promote products or services.
Design for climate change COP 28 UAE - UN Climate change Conference 2023
5th EIPF, Save the Earth before it is too late
Keywords: Graphic Design; Poster design; Typography; Information design